The influence of instructional on writing based on context toward reading interest - Riza Nusahak; Atmazaki Atmazaki; Abdurahman Abdurahman (International Conferences on Educational, Social Sciences and Technology)
Quasi experimental research with 2x2 factorial was designed to describe the influence of method-based context toward reading interest in writing skills. It was assumed that reading interest played an important role in writing and based approaches context would make it easier for students to produce their writing. The results shown that generally there were differences on students' writing product outcomesat SMKN-2 Sawahlunto with CTL (experiment) and conventional approaches (control), both that had high or low reading interest. In addition, there was a connection between approaches in learning and reading interest on students' success in writing exposition text. CTL approach affected high writing skill and reading interest. It is suggested that students' interest in reading is a concern to support writing exposition text.